Multiple uses of water in the Puraquequara River Basin, Manaus, Amazonas (Research, Society and Development, 2020)
A hydrographic basin is an integral part of the landscape, which allows biophysical, social and territorial planning interactions. This work aimed to identify and characterize the multiple uses of water in the Puraquequara River Basin, in Manaus. For this purpose, the survey of cartographic data was carried out, in addition to consultations on bibliographic materials. Then, two technical visits were made, one during the flood period and the other during the ebb. Thus, it was possible to elaborate thematic maps and image-cards, which allowed to initially identify the uses of water in the basin. In order to identify the other uses, technical visits were made by land and river, covering 7 km of the main river, downstream upstream, acquiring geographic coordinates. The results obtained proved that the Puraquequara river basin has a direct influence on the sustainability of economic activities and subsistence, making the use of water vital for the development of local populations. I find heterogeneous scenarios of use for the basin: irrigation activities, sand exploration, damming of tributaries by means of a dam, excavation of tanks for fish farming are downstream. Upstream, there is a predominance of riverside, floating communities, the meat industry and the shipping industry.